Glucocorticoids: mechanisms of action and anti-inflammatory potential in asthma - V. H. J. van der Velden (Hindawi Limited, 1998)
Glucocorticoids are potent inhibitors of inflammatory processes and are widely used in the treatment of asthma. The anti-inflammatory effects are mediated either by direct binding of the glucocorticoid/glucocorticoid receptor complex to glucocorticoid responsive elements in the promoter region of genes, or by an interaction of this complex with other transcription factors, in particular activating protein-1 or nuclear factor-κB. Glucocorticoids inhibit many inflammation-associated molecules such as cytokines, chemokines, arachidonic acid metabolites, and adhesion molecules. In contrast, anti-inflammatory mediators often are up-regulated by glucocorticoids. In vivo studies have shown that treatment of asthmatic patients with inhaled glucocorticoids inhibits the bronchial inflammation and simultaneously improves their lung function. In this review, our current knowledge of the mechanism of action of glucocorticoids and their anti-inflammatory potential in asthma is described. Since bronchial epithelial cells may be important targets for glucocorticoid therapy in asthma, the effects of glucocorticoids on epithelial expressed inflammatory genes will be emphasized.